Expression Analysis of Differentiated Sago Palm gene (Phosphate transporter and Detoxification Protein) via Amplified cDNA - LIEYEU, CHIOK (Universiti Malaysia Sarawak (UNIMAS), 2022)
Metroxylon Sagu (Sago palm) is an important tropical plant and important starch source in Malaysia. However, the presence of the stunted phenotype of sago palm had largely reduced the economic value of the plant and the problem remains one of the major concerns of the whole sago plantation till these days. The present study looks at expression analysis of differentiated sago palm gene using amplified cDNA. The Phosphate transporter gene and Detoxification protein gene were selected to be used to design the primer for amplifying the cDNA. CTAB-buffer was used to extract the total mRNA from the sago leaf. The expression level of the phosphate transporter was found to be similar between the trunking and non-trunking species of the sago palm. While the expression of the detoxification protein was showed poorly expressed in trunking species and not expressed in the non-trunking species. Further research on the above-mentioned factors for Metroxylon sagu should be conducted due to its high potential in starch production and commercialized products.